Public policies fundamental part of the colombian post-conflict (2016)
The Colombian post-conflict is a process that involves us each of us regardless of whether the armed conflict has affected us directly or indirectly in our lives and development of daily activities, but the main responsibility of this process involves the Colombian Government through the public administration in its entirety and articulation itself, which is required to restructure and generate new public policies that allow it to carry out a successful process of reintegration of demobilized combatants into civilian life. These policies should be included in the agendas of government to carry out the process of pregnancy, formulation, implementation and evaluation, development of this cycle determines the success or failure of public policy in its entirety, especially in a subject so hub for Colombian society as is the post-conflict, which occurs after an armed conflict for over fifty years and for which we are not fully prepared to face the process of forgiveness and reconciliation. Hence the importance of proper development of public policies that allow for the full integration of demobilized society, Political Life, Education, Labor and other socio-economic factors in the country, prioritizing and cornerstone policy of reparation for victims of armed conflict with the FARC-EP, to a successful post-conflict process.